Influence of fish feeds on sediment quality and macrofaunal assessment in fish farms - Gajo, Princess Lean Tubato
This study investigated the influence of fish feeds on sediment quality through microcosm and field survey. The result of microcosm experiment showed that feed treatments resulted to negative redox potential values (-103 to -138 mV) suggesting hypoxia. The total sulphides (0.03 to 2.50 mg g-1), TOM (5.33 to 7.11%) and total protein (9.30 to 49.65 mg g-1) were significantly higher in feed-treated sediments than the control. Fish feed with plant proteins (soybean and wheat meal) significantly increased total protein (49.65 mg g-1) than fish meal-based feed (34.15 mg g-1). Ammonium-nitrogen concentrations in high feed input of fish feed with soybean and wheat meal (310.45 ppm pore water; 635.90 ppm surface water) were higher than fish meal-based feed (249.42 ppm pore water; 405.35 ppm surface water). Field survey showed that off-cage area had aerobic condition characterized by positive redox potential (+4 mV) while fish cage areas had hypoxic (-99 mV) to anoxic (-235 mV) conditions. The total protein in fish cage areas (44.80 to 38.85 mg g-1) was significantly higher than the off-cage area (25.31 mg g-1). Higher concentrations of moisture and total sulphides were also significantly observed in fish cages than the off-cage area. Moreover, macrofaunal assessment showed a reduced diversity in organically-loaded fish farms. Absence of polychaetes in fish farm sediments implied a highly reduced condition and high sulphate reduction rate. The abundance of molluscs in sediments and net biofouling indicated a high degree of organic enrichment.